2002
DOI: 10.1063/1.1478793
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of reverse-bias leakage current in Schottky diodes on GaN grown by molecular-beam epitaxy using surface modification with an atomic force microscope

Abstract: The characteristics of dislocation-related leakage current paths in an AlGaN/GaN heterostructure grown by molecular-beam epitaxy and their mitigation by local surface modification have been investigated using conductive atomic force microscopy. When a voltage is applied between the tip in an atomic force microscope ͑AFM͒ and the sample, a thin insulating layer is formed in the vicinity of the leakage paths where current is observed. As the insulating layer reaches a thickness of 2-3 nm, the leakage current is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 16 publications
3
67
1
Order By: Relevance
“…The procedure used to perform CAFM is described elsewhere. 3 The measured tip-sample currents for the unmodified and modified surfaces are shown in Figs. 2͑a͒ and 2͑b͒, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure used to perform CAFM is described elsewhere. 3 The measured tip-sample currents for the unmodified and modified surfaces are shown in Figs. 2͑a͒ and 2͑b͒, respectively.…”
mentioning
confidence: 99%
“…2 Previous studies have shown that these leakage paths can be blocked by the formation of insulating layers over these leakage paths using an atomic force microscope ͑AFM͒. 3 Because this process is not practical as a large-scale surface treatment due to the time-intensive nature of the AFM surface modification procedure, an alternative technique suitable for efficient treatment of large surfaces would be desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al [41] also observed dislocation-related leakage paths in AIGaN/GaN heterostructures. In addition, they demonstrated that the process of scanning with a voltage applied between the tip and sample can lead to the formation of an insulating layer (of gallium oxide) [42] over the dislocation.…”
Section: Investigation Of Defects By Spmmentioning
confidence: 87%
“…They employed scanning capacitance microscopy (SCM) to investigate threading dislocations in GaN. Since then, SCM [13][14][15], electrostatic force microscopy (EFM) [16][17][18][19][20], Kelvin probe force microscopy (KPFM) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36],conductive-tip atomic force microscopy (C-AFM) [35][36][37][38][39][40][41][42][43][44][45][46], piezoresponse force microscopy (PFM) [47][48][49][50] and scanning gate microscopy (SGM) [51] have all been employed to characterize III-nitride films and surfaces.…”
Section: Introductionmentioning
confidence: 99%